2010
DOI: 10.1107/s1600536810035762
|View full text |Cite
|
Sign up to set email alerts
|

(E)-1-(2-Furyl)-3-(2,4,6-trimethoxyphenyl)prop-2-en-1-one

Abstract: In the title heteroaryl chalcone derivative, C16H16O5, the dihedral angle between the furan and benzene rings is 14.45 (6)°. The three meth­oxy groups are almost coplanar with their attached benzene ring [C—C—O—C torsion angles = 2.07 (17), −5.04 (17) and 2.85 (16)°]. An intra­molecular C—H⋯O hydrogen bond occurs. In the crystal, adjacent mol­ecules are linked into X-shaped chains along the c axis by weak C—H⋯O(enone) inter­actions. These chains are stacked along the b axis. C⋯O [3.3308 (13)–3.4123 (14) Å] sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
(13 reference statements)
3
8
0
Order By: Relevance
“…In each molecule, intramolecular C-H•••O weak interaction (Table 1) generates S(6) ring motif (Bernstein et al, 1995). The bond distances agree with the literature values (Allen et al, 1987) and are comparable with those observed in related structures (Chantrapromma et al, 2009;Fun et al, 2010Fun et al, , 2011Suwunwong et al, 2009).…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…In each molecule, intramolecular C-H•••O weak interaction (Table 1) generates S(6) ring motif (Bernstein et al, 1995). The bond distances agree with the literature values (Allen et al, 1987) and are comparable with those observed in related structures (Chantrapromma et al, 2009;Fun et al, 2010Fun et al, , 2011Suwunwong et al, 2009).…”
Section: Methodssupporting
confidence: 87%
“…For related literature on hydrogen-bond motifs, see: Bernstein et al (1995). For related structures, see: Chantrapromma et al (2009); Fun et al (2010Fun et al ( , 2011; Suwunwong et al (2009). For background to and applications of chalcones, see: Go et al (2005); Liu et al (2008); Ng et al (2009); Ni et al (2004); Suwunwong et al (2011); Tewtrakul et al (2003).…”
Section: Related Literaturementioning
confidence: 99%
“…In the molecule, a weak intramolecular C7-H7A•••O4 interaction (Table 1) generates an S(6) ring motif (Bernstein et al, 1995). The bond distances are of normal values (Allen et al, 1987) and comparable with related structures (Chantrapromma et al, 2009;Fun et al, 2010;.…”
Section: Data Collectionmentioning
confidence: 70%
“…For hydrogenbond motifs, see: Bernstein et al (1995). For related structures, see: Chantrapromma et al (2009); Fun et al (2010Fun et al ( , 2011. For background to and applications of chalcones and heteroaryl chalcones, see: Bandgar et al (2010); Gacche et al (2008); Go et al (2005); Isomoto et al (2005); Jung et al (2008); Suwunwong et al (2011); Tewtrakul et al (2003).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation